2017
DOI: 10.1590/1516-3180.2017.0058200317
|View full text |Cite
|
Sign up to set email alerts
|

What do Cochrane systematic reviews say about interventions for autism spectrum disorders?

Abstract: CONTEXT AND OBJECTIVE: Autism spectrum disorders (ASDs) include autistic disorder, Asperger's disorder and pervasive developmental disorder. The manifestations of ASDs can have an important impact on learning and social functioning that may persist during adulthood. The aim here was to summarize the evidence from Cochrane systematic reviews on interventions for ASDs. DESIGN AND SETTING: Review of systematic reviews, conducted within the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina, Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
(88 reference statements)
0
32
0
5
Order By: Relevance
“…Systematic reviews of the evidence base for treatment have been completed on early intensive intervention, 44,300 medical treatments, 301 behavioral interventions, 294,298 and evidencebased practice guidelines. 292,302 Wong et al 295 295,303 Focused intervention practices are designed to address a single or limited range of skills, such as increasing social communication or learning a specific task, and may be delivered over a short period of time.…”
Section: Section 5: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews of the evidence base for treatment have been completed on early intensive intervention, 44,300 medical treatments, 301 behavioral interventions, 294,298 and evidencebased practice guidelines. 292,302 Wong et al 295 295,303 Focused intervention practices are designed to address a single or limited range of skills, such as increasing social communication or learning a specific task, and may be delivered over a short period of time.…”
Section: Section 5: Interventionsmentioning
confidence: 99%
“…Although these behaviors are not core features of ASD, they commonly interfere with functioning in school, at home, and in the community and contribute substantially to the challenges faced by families. 293,294,381,[452][453][454][455][456][457] Psychiatric conditions (such as ADHD, anxiety, OCD, mood disorders, conduct disorders, or others) are identified in 70% to 90% of children and youth with ASD. 458,459 Behavioral challenges have a significant effect on health and quality of life for children and adolescents with ASD and their families.…”
Section: Co-occurring Behavioral Health Conditionsmentioning
confidence: 99%
“…In 1998, a case series reported secretin in amelioration of the symptoms in three ASD children (Horvath et al, 1998). However, later double-blind placebo-controlled clinical studies revealed that there was a lack of significant impact of secretin in the treatment of ASD symptoms (Esch and Carr, 2004;Malone et al, 2005;Krishnaswami et al, 2011;Lyra et al, 2017). In spite of the failure in clinical studies, animal obervations support the roles of secretin in some social functions.…”
Section: Secretinmentioning
confidence: 99%
“…However, failures are frequently reported when directly trying the administration of those peptides to ameliorate autistic behaviors. For example, one clinical trial failed to detect significantly improvement of social phobia by using CCK-tetrapeptide (CCK-4) (Katzman et al, 2004), and many double-blind placebocontrolled studies using secretin to alleviate autism symptoms infusion have also been failed (Esch and Carr, 2004;Malone et al, 2005;Krishnaswami et al, 2011;Lyra et al, 2017) even though the existence of one early study reporting the beneficial effects of secretin (Horvath et al, 1998). Therefore, major challenges are faced by those gut hormones probably due to their rapid turnover in vivo and low efficiency for penetrating the blood brain barrier (BBB).…”
Section: Implications For Autism Drug Developmentmentioning
confidence: 99%
“…Аналогичные работы последних лет, целью которых явилась попытка систематизировать данные в отношении эффективности диетотерапии при расстрой-ствах аутистического спектра, также указывают на недоста-точную доказательную базу и необходимость проведения дополнительных, хорошо организованных клинических исследований. При этом авторы вовсе не отрицают возмож-ную эффективность безглютеновой диеты, принимая во внимание субъективное мнение родителей пациентов и положительные результаты отдельных работ [27,28].…”
unclassified